Heavy poaching in prime habitat: the conservation status of the West Indian manatee in Nicaragua - Jiménez, Ignacio (2002)
This study provides an overview of the conservation status of the West Indian manatee Trichechus manatus in Nicaragua, including data on habitat availability, manatee distribution and relative abundance, and current threats. The data is based on surveys from boats and extensive interviews with local people. Nicaragua harbors one of the largest areas of habitat suitable for manatees in Central America. The species has an almost continuous distribution along the country's eastern, Caribbean coast and inland in some watercourses. There are larger groups of manatees in brackish lagoons than in freshwater rivers. Seasonal migrations and lengthy daily travels influenced by tides have been reported. The main threats to these manatees include poaching and incidental drowning in fishing nets, while boat traffic, pollution and habitat loss presently seem to be negligible factors in Nicaragua. Poaching is widespread along the coast and it is estimated that c. 40 manatees are killed annually throughout the country. Enforcement of hunting laws and protected areas is almost non-existent, with the exception of the Southeastern Nicaragua Biosphere Reserve. This may explain why manatees have disappeared from a few areas and become rare in others. Unless restrictions are imposed on poaching and on the use of gill nets within inland wetlands, the West Indian manatee may become rare throughout Nicaragua in the near future.